Single Mothers in Poverty in Brazil: Repercussions on Quality of Life and Anxiety for Pregnant and Postpartum Women. - Dal'Ava Dos Santos, Laura Mendes Toledo; Buccini, Gabriela; Pedroso, Jéssica; Schincaglia, Raquel Machado; de Toledo Vianna, Rodrigo Pinheiro; de Lima, Rafaela Lira Formiga Cavalcante; Viana, Maria Augusta Correa Barroso Magno; Gubert, Muriel Bauermann (Journal of Poverty)
We aimed to identify whether single mother in poverty is a risk factor for household food insecurity, anxiety, and poor quality of life and whether extreme poverty modifies this association. The study included 545 pregnant women or mothers with a monthly per capita income less than half the minimum wage. Single mother is associated with anxiety and poor quality of life in the psychological, physical, and social relationship domains, compared to mothers with a partner. Single mothers in the situation of extreme poverty had higher odds of having trait anxiety and a lower quality of life in the psychological domain.